The «Spectators» and their influence on the Press in Cádiz in the 18th Century and the Spanish War of Independence: a Successful Model in a Changing Society - Beatriz SÁNCHEZ HITA (Cuadernos Dieciochistas)
This paper shows the influence of certain characteristics of the «spectators», the most important journalistic format of enlightenment, in the miscellaneous publications appearing at the end of the eighteenth-century, and also in the various public papers of the Spanish War of independence. in this last period, thanks to freedom of the press, journalism experiences a second golden age and becomes a sort of fourth power with influence over political life; it is at this time that criticism of customs evolves to a real project of social transformation.